Optimizing Islamic Boarding School-Based Branding to Increase the Reputation of Islamic Higher Education - A. Faizin; Yatim Riyanto; M.V. Roesminingsih (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The main objectives of this research are to identify effective branding strategies, understand the impact of implementing Islamic boarding school-based branding on the university's reputation, and explore the role of Islamic boarding school values ​​in building a positive image of the institution. Method: The method used in this research is a qualitative approach with a case study design. Data was collected through in-depth interviews, participant observation, and document analysis. Results: The research results show that integrating Islamic boarding school values ​​in the curriculum, using social media for promotion, and collaborating with alums and Islamic boarding school figures are effective branding strategies in improving the university's reputation. Implementing these strategies has succeeded in increasing the attractiveness of Qomaruddin Gresik University in the eyes of prospective students and the wider community and strengthening alum loyalty. This research also found that Islamic boarding school-based branding can provide a strong and unique identity for the university, differentiating it from other Islamic universities. Novelty: This research emphasizes a holistic approach to optimizing Islamic boarding school-based branding, focusing not only on promotional aspects but also on integrating Islamic boarding school values ​​in all aspects of university operations.